Is Overwork Culture a New Normal? Rethinking from Psychological Detachment Perspective.: Life Sciences - Barik, Smita; Yadav, Dr. Jaya (International Journal of Life Science and Pharma Research, 2023)
Previous studies have shown and proven that employees need temporary detachment from their work to recharge and re-energize for the next day to work with similar enthusiasm. But work pressures and overwork culture have become a buzzword every corporate follows, and employees are bound to face it. This study investigates the impact of overwork culture (OWC) on employee longevity (EL). Further, it examines the mediating role of employee psychological detachment (EPD) on the linkage between OWC and EL. It aims to develop a relationship between psychological detachment and employee longevity, which can be referred to further to show how important the former’s role is for the organization’s welfare. The survey data was collected from 116 IT professionals from India, and the proposed relationship was analyzed through the SMART – PLS structural equation modeling tool. This study found a significant impact of Overwork Culture on EPD, but at the same time, the impact of OWC on EL is much less. This gives a scope to rethink the causes behind accepting this new norm. Also, our study fails to give the considerable impact of EPD on EL, and the mediating role of EPD can decrease up to 13% of the impact of OWC on EL. The originality of the research stems from the scarcity of research on EPD and almost no study on the mediating role of EPD on EL. This is one of the earliest studies to investigate the mediating role of EPD on EL with another independent variable. This proves the novelty of this study as it has a huge difference after Covid-era, where psychological detachment has less effect on employee longevity.